ANALISA DESAIN KEKUATAN STUKTUR PART KONEKTOR DAN TUBE FRAME UAV VTOL MENGGUNAKAN FINITE ELEMENT ANALYSIS - Mario Fernandez; Dhimas Wicaksono; Ferry Setiawan; Muhammad Kevin Adam (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2023)
UAV The purpose of this study was to determine the effect of the use of carbon fiber and aluminum materials on the structural strength of the tube and connector parts by considering the safety factor obtained from the analysis results. This study uses the finite element method with the help of solidworks software. The research was conducted in stable flight conditions, namely the UAV's gravity was the same as the UAV's lift. From the results of the frame design, the weight mass is 25.6 kg. From the simulation results, the tube with carbon fiber material and aluminum 6061 alloy both have good strength because the maximum stress values ​​that occur are 15.71 MPa and 15.64 MPa, and these values ​​are still below the yield stress of carbon fiber material which is 551 MPa and aluminum 6061 alloy material, namely 55.1 MPa, with a safety factor obtained of 35 for carbon fiber and 3.5 for aluminum 6061 alloy, and a maximum displacement of 0.056 mm for carbon fiber and 0.812 mm for aluminum 6061 alloy. Whereas the connectors with carbon fiber and aluminum 6061 alloy materials also have good strength because the maximum stress values ​​that occur are 4,266 MPa and 4,139 MPa, and these values ​​are still below the yield stress of carbon fiber material and aluminum 6061 alloy material. with a safety factor obtained of 130 on carbon fiber and 3.5 on aluminum 6061 alloy, and the maximum displacement is 3,734 x 10-5 mm on carbon fiber and 5,416 x 10-4 mm on aluminum 6061 alloy. The use of carbon fiber material in tubes and connectors has better strength than aluminum 6061 alloy, due to the safety factor the value obtained is greater.